A rare structural myopathy: Nemaline myopathy - Yeşilbaş, Osman (Turk Pediatri Ars, 2019)
Nemaline myopathy, which is characterized by the accumulation of ‘’rod’’ bodies in muscle fibers is a very rare inherited muscle disease. According to the underlying mutation, the disease has varying severity of clinical outcomes. Patients with severe forms of the disease die because of hypotonia, feeding difficulties, aspiration pneumonia, and respiratory failure in the neonatal or infancy period. Mild forms of the disease present with walking-swallowing difficulties and respiratory distress in late childhood or adulthood. A two-and-a-half-month-old boy was monitored in our Pediatric Intensive Care Unit with hypotonia, pneumonia, and respiratory distress. Nemaline myopathy was diagnosed as the result of a muscle biopsy. An advanced molecular examination revealed heterozygous mutations in the skeletal muscle α-actin (ACTA1) gene, which is the second most common cause of this disease. Nemaline myopathy should be kept in mind in patients of all age groups with respiratory failure and walking difficulty secondary to muscle weakness.